A SEMANTIC ANALYSIS OF ORAL TRADITION TAWA TASAPO: WHEN WORDS CAN BE A MEDICINE - Oktri Frantika; Rusdi Noor Rosa (English Language and Literature, 2019)
Tawa tasapo is one of the examples of oral tradition that persists in traditional medicine in Solok Regency. This research aimed to see linguistics meaning of language in tawa tasapo. The analysis was done by the application of Leech theory of meaning that divide meaning into seven types of meaning: conceptual, connotative, social, affective, reflective, collocative, and thematic meaning. This research used descriptive-qualitative method with simple mathematic to determine the finding of this research. After analyzing the data, it was found that connotative meaning and social meaning as the dominant used in this research. The result was influenced by Minangkabau and Islam culture.